Deciphering Neuro-Ophthalmic Presentations of Carotid Cavernous Fistulas: A Comprehensive Analysis of Venous Flow Dynamics and Clinical Implications - Al-Shalchy, Ali; Al-Wassiti, Ahmed; Hashim, Mohammed; Ismail, Mustafa (AL-Kindy College Medical Journal, 2024)
Background: Carotid cavernous fistulas (CCFs) are abnormal arteriovenous connections between the carotid arterial system and the cavernous sinus, presenting with complex neuro-ophthalmic manifestations due to the redirection of arterial blood into the venous system. This study systematically reviews the diverse neuro-ophthalmic presentations of CCFs, emphasizing the influence of venous flow dynamics. Methods: A comprehensive literature search was conducted in PubMed, Scopus, and Web of Science, focusing on keywords such as "carotid cavernous fistula," "neuro-ophthalmic presentations," and "optic nerve compression." Recent and historical studies were analyzed to assess the neuro-anatomical impacts on neuro-ophthalmic symptoms from CCFs. This review aimed to consolidate knowledge and refine diagnostic and therapeutic strategies for CCF management. Results: The findings demonstrated that the neuro-ophthalmic presentations were quite distinctive, depending on the direction of venous flow. Anterior flow, overall, was associated with proptosis, conjunctival arterialization, and red, dilated vessels. In contrast, posterior flow was associated with cranial nerve complications, most notably abducens nerve palsy and trigeminal neuralgia, manifesting as double vision and facial pain, respectively. It therefore seems that the symptomatology and severity of CCFs is heavily dependent on the direction of blood flow. Conclusion: The flow direction through the veins is of significant importance in the clinical presentation and prognosis of CCFs. These dynamics must be appreciated to improve diagnosis and allow for optimal treatment, thus averting the risk of fatal complications. In this review, the need for tailored therapeutic strategies through detailed vascular and neuro-ophthalmologic analysis is outlined.